Electronic properties of C60 crystals: why we need crystals grown in a microgravity? - Kveder, V. V.; Nikolaev, R. K.; Steinman, E. A.; Ossipyan, Yu. A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1998)
The crystalline fullerene C60 is a novel semiconductor very interesting for basic science and for possible applications. It corresponds to intermediate case between &quotclassical&quot semiconductors (like Si or GaAs) and &quotclassical&quot molecular crystals. Therefore, some interesting effects related to insulator-metal transitions and electron correlation can be possibly discovered in C60 crystals. In spite of numerous investigations, the electronic properties C60 crystals are still far from clear understanding. It is even not clear to what extent it is possible to consider the solid C60 as one-electron band-like semiconductor. The main reason for that is the very high defect concentration in the crystals available now. In the present report we discuss some experimental data concerning the electronic properties of C60 crystals and the existing problems in their interpretation. We also discuss the reasons why the crystals grown in normal gravitation have many defects and why there is a good chance to produce much more perfect crystals in a microgravity conditions.